Identification and analysis of divergent immune gene families within the Tasmanian devil genome. (December 2015) - Morris, Katrina; Cheng, Yuanyuan; Warren, Wesley; Papenfuss, Anthony; Belov, Katherine
Abstract Background The Tasmanian devil (Sarcophilus harrisii ) is being threatened with extinction in the wild by a disease known as devil facial tumour disease (DFTD). In order to prevent the spread of this disease a thorough understanding of the Tasmanian devil immune system and its response to the disease is required. In 2011 and 2012 two genome sequencing projects of the Tasmania devil were released. This has provided us with the raw data required to begin to investigate the Tasmanian devil immunome in depth. In this study we characterise immune gene families of the Tasmanian devil. We focus on immunoglobulins, T cell receptors and cytokine families. Results We identify and describe 119 cytokines including 40 interleukins, 39 chemokines, 8 interferons, 18 tumour necrosis family cytokines and 14 additional cytokines. Constant regions for immunoglobulins and T cell receptors were also identified. The repertoire of genes in these families was similar to the opossum, however devil specific duplications were seen and orthologs to eutherian genes not previously identified in any marsupial were also identified. Conclusions By using multiple data sources as well as targeted search methods, highly divergent genes across the Tasmanian devil immune system were identified and characterised. This understanding will allow for the development of devil specific assays and reagents and allow for future studies into the immune response of the Tasmanian devil immune system to DFTD.